Manejo agronómico del cultivo de Hibiscus sabdarifa L. (Jamaica). - Suárez Rosero, María José (2022)
This document refers to the agronomic management of the cultivation of Hibiscus sabdarifa L. (Jamaica). Agronomic management, through the set of activities or tasks, aims to provide the crop with the best development and growth conditions in order to approach the crop's yield potential and obtain the best profitability results. The conclusions determine that it is necessary to carry out training pruning and tutoring in the plantation in order to improve the performance of cultural tasks, repeat research implemented the agronomic management of the Jamaican crop to determine its effect on yield, promote sowing trials of the cultivation in agricultural areas of Ecuador, according to what has been studied, the pruning carried out in the cultivation is the best work that affects the existence of greater production and the benefits of the flower of Jamaica, due to the concentration of bioactive compounds and the chemical and functional properties, It has been shown that its use as a beverage notably improves hypertension, diabetes and cancer, so consuming it frequently lowers blood pressure, which is why it is considered a cardiac tonic. It fights malignant cells for its help in the growth of defenses and the increase of antibodies in people suffering from cancer.